The Anatomical Investigation of the Arcus Aortae in Persian Squirrel (Sciurus Anomalus) - Javad Sadeghinezhad; Narges Zadsar; Soroush Bakhtiari Rad (Negah Institute for Scientific Communication, 2015)
Introduction: The Persian Squirrel (Sciurus anomalus) is the only member of the Sciuridae family found in the Middle East. Some people maintain them as pets, thus their referrals to veterinary hospitals has been increased recently. Several morphological studies have been carried out mainly on the arch of aorta and its branches in common rodents, small mammals, and domestic animals but there are no reports on the details of the arcus aortae and its branches in the Persian squirrel despite the massive distribution of this species. Therefore, this study aimed to investigate the anatomy of the arcus aortae in this species to promote future investigations in this field. Methods: Four adult Persian squirrels were used for this research. The subjects were injected with red-colored latex into their left ventricles. Then, they were dissected and the pattern of arcus aortae branches was illustrated in the Persian squirrel. Results: The arcus aortae branches off to the truncus brachiocephalicus and the arteria subclavia sinistra. At first the arteria carotis sinistra arises from the truncus brachiocephalicus and then continues to give off the arteria carotis dextra and arteria subclavia dextra. The subclavia dextra and sinistra branch into the same vessels, including arteria thoracica interna, arteria vertebralis, arteria cervicalis superficialis, arteria cervicalis profunda, and a common root which ramifies to the arteria scapularis dorsalis and the arteria intercostalis supreme. Conclusion: The vessels originating from the arcus aortae showed significant differences, especially in the arteria subclavia branches compared to other rodents and small mammals.